Investigation into the effects of surface condensation in steam-driven twin screw expanders / trans. from Engl. M. A. Fedorova - M. A. Fedorova (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
During the operation of twin screw expanders with slightly superheated vapours or even two-phase fluids, surface condensation on machine parts occurs during the filling period and the expansion phase when the working fluid is in contact with cooler inner surfaces. This heat exchange from the working fluid to adjacent machine parts effects the working cycle and the efficiency of these machines. Short time scales and the periodicity of the process indicate the condensation process is best described by models for dropwise condensation. In this paper the effects of surface condensation on the operation of twin screw expanders are initially discussed in a simulation-based investigation. Chamber model simulation coupled with a thermal analysis is used for the thermodynamic simulation, whereby heat transfer coefficients are systematically varied. It is found that during the inlet phase condensate emerges on the inner surfaces of the machine being substantially cooler than the working fluid. This results in a higher mass being trapped within the working chamber and, thus, an increasing mass flow rate of the machine. An increase in power output is, however, not observed. The results obtained from chamber model simulations are finally compared against experimental data of a screw expander prototype